Pott disease in the differential diagnosis of low back pain - Önal, S. Ateş; Özer, B. (My University, 2004)
Tuberculosis of skeletal system is frequently located in spine and is called as "Pott disease". Pott disease is frequently located in lumbar vertebrates and it can be interfered with the other diseases which cause low back pain. Our patient which was operated because of breast cancer nearly 10 years ago, has had waist and leg pain for 6 weeks. The story of breast cancer reminded us the possibility of a metastasis. But there were no findings in favour of metastasis except the high scores of sedimentation rate. There was a disc herniation according to the MR imaging of lumbar region. Therefore we performed epidural steroid injection but 10 days later the patient was unable to walk. We present this case to understand the importance of the differential diagnosis of Pott disease.
Bel a?risinin ayirici tanisinda Pott hastali?i
Keywords: Low back pain; Pott disease; Tuberculosis